2019
DOI: 10.3389/fpsyg.2019.02131
|View full text |Cite
|
Sign up to set email alerts
|

Low Rates of Pointing in 18-Month-Olds at Risk for Autism Spectrum Disorder and Extremely Preterm Infants: A Common Index of Language Delay?

Abstract: Infants with an older sibling with an Autism Spectrum Disorder diagnosis (Sibs ASD) are at high risk for language delay (LD) as well as infants born preterm, especially those with an extremely low gestational age (ELGA, GA ≤ 28 weeks). Gestures play a crucial role in language development and delays in gesture production may have negative cascading effects on it. The present exploratory study examined gesture production in 18-month-old infants with different underlying risks for LD. Seventy monolingual United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 78 publications
2
21
1
Order By: Relevance
“…As for the identification of early predictors (Q1), some studies examined the role of biological and environmental risk factors for DLD [ 75 , 76 , 77 , 78 , 79 ] and many provided potentially useful data about early gestural, communicative, lexical, and grammatical predictors [ 75 , 76 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the identification of early predictors (Q1), some studies examined the role of biological and environmental risk factors for DLD [ 75 , 76 , 77 , 78 , 79 ] and many provided potentially useful data about early gestural, communicative, lexical, and grammatical predictors [ 75 , 76 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even if none of the selected studies directly focused on the problem of the most appropriate age range for the use of screening and diagnostic tools (Q2), almost all of them provided indirect indications to answer Q2 [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…The strong relation between early pointing gestures and language skills is not only found in TD children, but also in children with high risk for developmental disorders, such as: siblings of children with autism spectrum disorder (Baron-Cohen et al, 1992;Parladé and Iverson, 2015;Iverson et al, 2018;Sansavini et al, 2019), extremely preterm infants (Benassi et al, 2018;Sansavini et al, 2019), and children with Down Syndrome (te Kaat-van den Os et al, 2015). However, there are hardly any studies about early pointing behavior within a comparatively large group of children, namely children with language delay (LD) and developmental language disorder (DLD).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies with siblings of children with autism spectrum disorder often comprise three different outcome groups: Siblings without developmental disorders, siblings with LD, and siblings with autism spectrum disorder (Parladé and Iverson, 2015;Iverson et al, 2018). From these studies we know that not only the siblings who turned out to be within the autism spectrum themselves, but also the siblings with a later diagnosis of LD produce a lower number of gestures early in their development and have a lower rate of initial growth in early gestures than TD children (Parladé and Iverson, 2015;Iverson et al, 2018;Sansavini et al, 2019). For children with LD, Bello et al (2018) found that conspicuously more of them do not produce declarative pointing gestures compared to TD children.…”
Section: Introductionmentioning
confidence: 99%
“…Two key areas of development characterize a diagnosis of autism spectrum disorder (ASD), hereafter “autism”: differences in social-communication (e.g., eye contact and interest in peers) and restricted, repetitive patterns of behavior (RRBs; e.g., fixated interests and stereotyped motor movements) ( 1 ). For children born preterm, there is a risk of early markers of autism, such as atypical eye gaze and protodeclarative pointing ( 2 ), being misattributed to the long-term effects from their preterm birth ( 3 ), as these can also be observed in children born preterm who do not go on to be diagnosed with autism ( 4 , 5 ), despite the higher than expected prevalence of autism in children born preterm ( 6 ). This has the potential to delay diagnosis and appropriate support.…”
Section: Introductionmentioning
confidence: 99%